Christianising Edgar Chagwa Lungu : The Christian nation, social media presidential photography and 2016 election campaign - Kaunda, Chammah J (Stellenbosch Theological Journal, 2018)
This article investigates how the declaration of Zambia as a Christian nation (hereafter the Declaration), presidential photography and social media intersected during Edgar Lungu's political campaign in the general election of 2016. It is framed within a missio-political theory to analyse qualitative material collected from January 2016 to February 2018 in Zambia. The missio-ethnography approach as an empirical missiological research which sought to analyse how the Declaration discourse has developed into a political ideology used to legitimized Lungu's political power and moral authority among some Pentecostal-Charismatic religious sector.